STUDI PERBANDINGAN PONDASI TIANG PANCANG DAN TIANG BOR DITINJAU DARI BIAYA DAN PRODUKTIVITAS TENAGA KERJA - Ningsih, Sri Aliane Rahayu; Setiawan, Agustinus Agus; Arbaningrum, Rizka (Universitas Tarumanagara, 2023)
The foundation is a sub structure element of a construction which has the function of distributing the load of the upper structure to the hard soil layer. This research has an objective to analyze the effectiveness of pile and drilled pile foundations in terms of costs and labor productivity. As a case study, the research object was taken from the implementation of the foundation structure of